Surgical removal of omental fat does not improve insulin sensitivity and cardiovascular risk factors in obese adults - Fabbrini, Elisa (2010)
BACKGROUND & AIMS: Visceral adipose tissue (VAT) is an important risk factor for the metabolic complications associated with obesity. Therefore, a reduction in VAT is considered an important target of obesity therapy. Therefore, we evaluated whether reducing VAT mass by surgical removal of the omentum, improves insulin sensitivity and metabolic function in obese patients. METHODS: We conducted: 1) a 12-month randomized controlled trial to determine whether reduction in VAT by omentectomy in 22 obese subjects enhances Roux-en-Y gastric bypass (RYGB) surgery-induced improvement in hepatic and skeletal muscle insulin sensitivity, assessed by using the hyperinsulinemic-euglycemic clamp technique, and 2) a 3-month longitudinal single-arm study to determine whether laparoscopic omentectomy alone in 7 obese subjects with type 2 diabetes mellitus (T2DM) improves insulin sensitivity, assessed by using the Frequently Sampled Intravenous Glucose Tolerance Test. RESULTS: The greater omentum, weighing 0.82 kg (95% CI: 0.67–0.97) was removed from subjects who had omentectomy in both studies. In study 1, muscle insulin sensitivity (relative increase in glucose disposal during insulin infusion) approximately doubled and hepatic insulin sensitivity increased by ~4-fold at 12 months after RYGB alone and RYGB plus omentectomy compared with baseline (P<0.001). There were no significant differences between groups (P>0.87) or group×time interactions (P>0.36). In study 2, surgery had no effect on insulin sensitivity (P=0.844) and use of diabetes medications. CONCLUSIONS: These results demonstrate that decreasing VAT through omentectomy, whether performed alone or in combination with RYGB surgery, does not improve metabolic function in obese patients.